Exploring the role of hand gestures in learning novel phoneme contrasts and vocabulary in a second language - Kelly, Spencer D.; Hirata, Yukari; Manansala, Michael; Huang, Jessica (Frontiers in Psychology, 2014)
Co-speech hand gestures are a type of multimodal input that has received relatively little attention in the context of second language learning. The present study explored the role that observing and producing different types of gestures plays in learning novel speech sounds and word meanings in an L2. Naïve English-speakers were taught two components of Japanese—novel phonemic vowel length contrasts and vocabulary items comprised of those contrasts—in one of four different gesture conditions: Syllable Observe, Syllable Produce, Mora Observe, and Mora Produce. Half of the gestures conveyed intuitive information about syllable structure, and the other half, unintuitive information about Japanese mora structure. Within each Syllable and Mora condition, half of the participants only observed the gestures that accompanied speech during training, and the other half also produced the gestures that they observed along with the speech. The main finding was that participants across all four conditions had similar outcomes in two different types of auditory identification tasks and a vocabulary test. The results suggest that hand gestures may not be well suited for learning novel phonetic distinctions at the syllable level within a word, and thus, gesture-speech integration may break down at the lowest levels of language processing and learning.